Strong, omnidirectional radar backscatter from subwavelength, 3D printed metacubes. Issue 14 (23rd September 2020) - Powell, Alex W.; Ware, John; Beadle, Joseph G.; Cheadle, David; Loh, Tian Hong; Hibbins, Alastair P.; Sambles, J. Roy
Abstract : Metallic metacubes formed of six metal plate faces connected via a metal jack are shown to backscatter microwave radiation extremely powerfully. Experimental radar scattering cross‐section (RCS) data from three‐dimensional (3D) printed samples agrees very well with numerical model predictions, showing a monostatic RCS of 15 times the geometric cross‐section. The principal resonance of the metacubes demonstrates near‐complete independence of the incident angle or polarisation of the radiation, making the metacube an omnidirectional scatterer. The metacubes are fabricated via additive manufacturing from metal‐coated polymer, and are extremely lightweight, making them excellent candidates for improving the radar return signals from small objects such as drones and cubesats.